A preliminary study on depression experienced by university students / Normala Ismail and Mohamad Kamil Ariff Khalid - Ismail, Normala; Khalid, Mohamad Kamil Ariff (Universiti Teknologi MARA, Sabah, 2022)
Since the Movement Control Order (MCO) came into force on 18 March 2020, Teaching and Learning from Home have been implemented to provide continuous education to students without the risk of contracting the COVID-19 virus. After two years have passed, students are advised to return to campus. They have begun studying face-to-face or in a hybrid manner. One of the difficulties faced is identifying the level of depression experienced by students in the transition environment from Teaching and Learning from Home to face-to-face or hybrid learning. Therefore, this study tries to identify the level of depression among the Third Semester Diploma in Management and Office Technology students from the Faculty of Business and Management at Universiti Teknologi MARA (UiTM) Pahang Branch, Jengka Campus. The Beck Depression Inventory (Second Edition) was distributed to 110 students in four different classes from the same faculty. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 20. The Cross Tabulation analysis results showed that almost half of the students suffered from a depressive disorder. The findings of this study have very important implications.